Will the Gig Economy Prevail? /? - Crouch, Colin, 1944- (The future of capitalism series)
In this book, Colin Crouch takes a step back and questions the logic of the 'gig economy'. He shows how the idea of an employee - a stable status that involves a bundle of rights - has, despite many changes and threats, shown a curious persistence. It